(untitled) (Annals of Medical Research, 2021)
Aim: Neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) are an inexpensive inflammatory marker that can be easily obtained from the blood count and can be used in many chronic diseases. In our study, we aimed to investigate the relationship between fibrosis stage and NLR, PLR in patients with chronic hepatitis B virus (HBV). Materials and Methods: 173 patients with chronic HBV were included in the study. The demographic data and hemogram parameters of all patients were recorded. Histopathological data of the patients were documented. Accompanying comorbid diseases, medications and previous operations were questioned. In chronic HBV patients, fibrosis level was compared with hematological parameters. Results: A total of 173 patients, 100 (57.8%) of whom were male, were included in the study. As a result of the liver biopsy; mild fibrosis (steage/1-2) in 83(47.9%) patients, moderate fibrosis (steage/3-4) in 35(20.3%) patients and advanced fibrosis (stage/5-6) in 55(31.8%) patients. In advanced fibrosis group, liver function tests and bilirubin levels were significantly higher and albumin level was significantly lower (p<0.05). It was found that NLR level was significantly higher in moderate fibrosis than mild fibrosis, and PLR level was significantly lower in the advanced fibrosis group than in the mild and moderate fibrosis groups (p<0.05). Conclusions: We showed that there is a significant relationship between fibrosis level and NLR, PLR. However, with the available data, it does not seem possible to say that noninvasive methods can completely replace invasive procedures such as liver biopsy. Prospectively designed studies with larger patient participation are needed.